The effects of two relaxation techniques on psychomotor, psychological and physiological variables following repeated submaximal intensity exercise among school athletes - Hazwani Ahmad, Yusof@ Hanafi (Universiti Sains Malaysia, 2009)
The present study was undertaken with an objective to investigate the effects of two relaxation techniques on selected psychomotor (choice reaction time), psychological (rating of perceived exertion (RPE) and physiological (heart rate, oxygen consumption (V02)) variables following repeated sub-maximal intensity exercise. Twenty four physically active young males with the mean age of 14.1 ± 1.3 years, height 157.3 ± 6.1 em, weight 45.6 ± 7.2 kg, V02max 45.7 ± 4.2 ml.kg-1.min-1 and HRmax 205.9 ± 1.3 participated in this study. They were randomly divided into one of the three groups: Autogenic relaxation {AGR), progressive muscle rela'l(ation {PMR.) and a control group. AGR and PMR group were tested in two experimental sessions; prior to and after relaxation training. However, the control group performed the same experimental procedures except the relaxation training. Each experimental session consists of four trials, where they had to cycle at 60% V02max for I 0 minutes followed by 90% V02max for 2 minutes in each trial. Then, it is followed by 3-minute resting interval where choice reaction time (CRT) was tested. Furthermore, RPE, heart rate, and V02 were recorded at the end of each trial. The results of two-way repeated measure ANOV A revealed a non significant (p > .05) interaction between the groups across the experimental trials in all of the selected parameters. However, results of the main effect revealed a significant (p < .05) difference for experimental sessions for RPE and V02. Pair wise comparison analysis revealed a significant (p < .05) reduction in RPE value from prexi to post-intervention sessions for PMR group and a significant (p < .05) decrease in the value ofV02 from pre- to post-intervention exercise for AGR and control groups. Thus, this study concluded that both relaxation techniques did not differ in terms of choice reaction time, RPE, V02 and heart rate following repeated sub-maximal intensity exercise. However, when analysed separately, PMR appears to reduce RPE while AGR appears to reduce vo2.